Fibrosis in diabetes complications: Pathogenic mechanisms and circulating and urinary markers - Stephen R.F. Twigg (2008)
Diabetes mellitus is characterized by a lack of insulin causing elevated blood glucose, often with associated insulin resistance.Over time, especially in genetically susceptible individuals, such chronic hyperglycemia can cause tissue injury.One pathological response to tissue injury is the development of fi brosis, which involves predominant extracellular matrix (ECM) accumulation.The main factors that regulate ECM in diabetes are thought to be pro-sclerotic cytokines and protease/anti-protease systems.This review will examine the key markers and regulators of tissue fi brosis in diabetes and whether their levels in biological fl uids may have clinical utility.